N-Acetyl Cysteine Protects against Methamphetamine-Induced Dopaminergic Neurodegeneration via Modulation of Redox Status and Autophagy in Dopaminergic Cells. (27th September 2012) - Chandramani Shivalingappa, Prashanth; Jin, Huajun; Anantharam, Vellareddy; Kanthasamy, Anumantha; Kanthasamy, Arthi
Abstract : Methamphetamine- (MA-) induced neurotoxicity is associated with mitochondrial dysfunction and enhanced oxidative stress. Our previous study demonstrated that MA induces autophagy in a dopaminergic neuronal cell model (N27 cells). The cellular mechanisms underlying MA-induced autophagy and apoptosis remain poorly characterized. In the present study we sought to investigate the importance of GSH redox status in MA-induced neurotoxicity using a thiol antioxidant, N-acetylcysteine (NAC). Morphological and biochemical analysis revealed that MA-induced autophagy in N27 dopaminergic cells was associated with pronounced depletion of GSH levels. Moreover, pretreatment with NAC reduced MA-induced GSH depletion and autophagy, while depletion of GSH using L-buthionine sulfoximine (L-BSO) enhanced autophagy. Furthermore, treatment with NAC significantly attenuated MA-induced apoptotic cell death as well as oxidative stress markers, namely, 3-nitrotyrosine (3-NT) and 4-hydroxynonenal (4-HNE). Together, these results suggest that NAC exhibits significant protective effects against MA-induced dopaminergic cell death, presumably via modulation of the GSH level and autophagy. Collectively, our data provide mechanistic insights into the role of cellular GSH redox status in MA-induced autophagy and apoptotic cell death, and additional studies are needed to determine the therapeutic effectiveness of cellular redox modifiers in attenuating dopaminergic neurodegeneration in vivo .